FAKTOR-FAKTOR YANG MEMPENGARUHI AKUISISI PENGETAHUAN DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Samuel Andrean Yahya (Business Administration Department - Universitas Katolik Parahyangan, 2021)
The COVID-19 pandemic enforced schools and universities to shift from traditional face to face learning into online learning. Sudden educational shift brought difficulties for students who were struggling to understand and acquire knowledge from teachers during online learning. The purpose of this study is to explore factors influencing students’ knowledge acquisition during online learning and measuring online learning effectiveness. Based on the literature review, a model has been proposed with three factors that are expected to have significant impact on students’ knowledge acquisition during online learning. Technology infrastructure, individual factor, university factor are independent factors, while online learning effectiveness is dependent factor and knowledge acquisition acts as mediating variable. The primary data were collected through questionnaire given to active students from Department of Business Administration, Parahyangan Catholic University. 295 students submitted their response for the research. Validity analysis, reliability analysis, and hypotheses test were conducted using SPSS. The finding reveals that individual factor and university factor have significant positive impact on knowledge acquisition, while information technology has significant negative impact on knowledge acquisition. The results also showed that knowledge acquisition have significant positive impact on online learning effectiveness, and acts as mediating variable between individual factor and online learning effectiveness. Moreover, the results also revealed that online learning in Department of Business Administration has run effectively. Keywords: online, learning, effectiveness, knowledge, acquisition